The Classification of Hanafi Books - Salah Abu Al-Haj (My University, 2016)
I was interested in this research in an indispensable issue for a researcher in Islamic jurisprudence, which is the classification of Hanafi books. I mentioned the general reasons for the varying degrees of books according to their authors, the differences in their approaches in authoring, and the split of authoring to: rooting, basics, application, graduation and subsidiarity. I also showed the presence of two types of classification of Hanafi books: a type of books related to narration, and another type of books related to approved and accepted and refunded books. Then I talked about some issues related to books of «Thaher Ar-rewayah», and the types of books does not relate to Thaher Ar-rewayah. I elaborated talk in the classification of accepted books and Unacceptable books in terms of definition, examples, reasons, applications, and how to take advantage of each. I ended the search with most important in the results in it.

اهتممت في هذا البحث بقضيّة لا يستغني عنها باحث في الفقه الإسلامي، وهي بيان طبقات الكتب عند الحنفية، فذكرتُ الأسباب العامّة لتفاوت درجات الكتب بتفاوت حال المؤلّفين، واختلاف مناهجهم في التأليف، وانقسام التأليف إلى تأصيل وتقعيد، وإلى تطبيق وتخريج وتفريع، وبيَّنتُ وجود نوعين من الطبقات للكتب عند الحنفية: نوعٌ متعلّق بكتب ظاهر الرواية وغير ظاهر الرواية والنوازل، ونوعٌ متعلّق بكتب معتمدة ومقبولة ومردودة، وتعرضتُ لبعض قضايا متعلّقة بكتب ظاهر الرواية، وأنواع كتب غير ظاهر الرِّواية، وفصَّلتُ الكلام في طبقة الكتب المعتمدة وطبقة الكتب المقبولة وطبقة الكتب المردودة من حيث التّعريف والأمثلة والأسباب والتطبيقات وكيفيّة الاستفادة لكلٍّ منها، وختمته بأهم النتائج في البحث.
طبقات كتب الفقهاء عند الحنفية